Tropical Atlantic Contributions to Strong Rainfall Variability Along the Northeast Brazilian Coast. (22nd January 2015) - Hounsou-gbo, G. A.; Araujo, M.; Bourlès, B.; Veleda, D.; Servain, J.
Abstract : Tropical Atlantic (TA) Ocean-atmosphere interactions and their contributions to strong variability of rainfall along the Northeast Brazilian (NEB) coast were investigated for the years 1974–2008. The core rainy seasons of March-April and June-July were identified for Fortaleza (northern NEB; NNEB) and Recife (eastern NEB; ENEB), respectively. Lagged linear regressions between sea surface temperature (SST) and pseudo wind stress (PWS) anomalies over the entire TA and strong rainfall anomalies at Fortaleza and Recife show that the rainfall variability of these regions is differentially influenced by the dynamics of the TA. When the Intertropical Convergence Zone is abnormally displaced southward a few months prior to the NNEB rainy season, the associated meridional mode increases humidity and precipitation during the rainy season. Additionally, this study shows predictive effect of SST, meridional PWS, and barrier layer thickness, in the Northwestern equatorial Atlantic, on the NNEB rainfall. The dynamical influence of the TA on the June-July ENEB rainfall variability shows a northwestward-propagating area of strong, positively correlated SST from the southeastern TA to the southwestern Atlantic warm pool (SAWP) offshore of Brazil. Our results also show predictive effect of SST, zonal PWS, and mixed layer depth, in the SAWP, on the ENEB rainfall.